Ready, set, action: cortical control of movement - Ivry, Richard (Henry Stewart Talks, 2010)
Anatomy of the motor pathways, Disorders of the motor system, Hemispheric asymmetries in motor control, Functional organization of the cortical motor system, Cellular representation of movement, Applications for motor rehabilitation, Brain-machine interface systems
Updated at 2021/04/30